A literature review exploring the preparation of mental health nurses for working with people with learning disability and mental illness. Issue 2 (March 2015) - Adshead, Stephanie; Collier, Elizabeth; Kennedy, Sarah
Abstract: The aim of this literature review is to explore whether mental health nurses are being appropriately prepared to care for learning disabled patients who also suffer from mental ill health. A systematic approach was adopted in order to identify relevant literature for review on the topic. Five electronic databases were searched; CINAHL, Medline, ERIC, PubMed and Scopus. Searches were limited to the years 2001–2013. A total of 13 articles were identified as relevant to the topic area for review. Three main themes were identified relating to (a) attitudes (b) practice and (c) education. There appears to be a lack of research that directly addresses this issue and the existing literature suggests that there are considerable deficits in the ability of mental health nurses to be able to provide appropriate care for those with both a learning disability and mental ill health. The findings of this review would suggest that this topic area is in urgent need of further investigation and research. Further research into this area of practice could possibly help to inform education regarding this subject at pre-registration and post qualifying levels, which could therefore in turn, improve the delivery of mental health nursing care to this particular client group.